The Significance of Early Alpha-Fetoprotein Level Changes in Predicting Clinical and Survival Benefits in Advanced Hepatocellular Carcinoma Patients Receiving Sorafenib - Yau, Thomas (AlphaMed Press, 2011)
BACKGROUND. The role of serum alpha-fetoprotein (AFP) changes in predicting the treatment outcomes of advanced hepatocellular carcinoma (HCC) patients to sorafenib remains unknown. METHODS. Serum AFP was collected prospectively at baseline and subsequent follow-up visits in parallel with clinical and survival outcomes. AFP response was defined as a relative drop of AFP >20% of the baseline level after 6 weeks of sorafenib. The relationship between AFP response and the treatment outcomes was first explored in patients who received sorafenib in a phase II study. Subsequently, an independent validation set of patients were obtained to validate the association of AFP response to clinical outcomes. RESULTS. Included in the exploration and validation sets for analysis were 41 and 53 patients, respectively, with baseline AFP level >20 μg/L. In the exploration cohort, AFP response was significantly associated with clinical benefit (CB) rate (relative chance 3.4, 95% confidence interval [CI], 1.1–11.1), and multivariate analysis indicated that AFP response was associated with significantly better progression-free survival (PFS) (hazard ratio [HR], 0.31; 95% CI, 0.13–0.76) and marginally better overall survival (OS) (HR, 0.30; 95% CI, 0.09–1.02). When applying AFP changes in the validation set, significant associations were again found between AFP response with CB rate (relative chance, 5.5; 95% CI, 2.3–13.6) and PFS (HR, 0.12; 95% CI, 0.04–0.30) but not OS (HR, 0.61; 95% CI, 0.27–1.26). CONCLUSION. Drop in AFP level at 6 weeks is an exploratory early surrogate for both CB and PFS in advanced HCC patients receiving sorafenib.